The management and long-term outcomes of endoscopic and surgical treatment of early esophageal adenocarcinoma. Issue 9 (22nd February 2020) - Saunders, John H; Al-Zubaidi, Samim; Waller, Ruth C; Ortiz-Fernandez-Sordo, Jacobo; Parsons, Simon L; Ragunath, Krish; Kaye, Philip V
Summary: Endoscopic resection (ER) for early (pT1) esophageal adenocarcinoma can be justified if the rate of coexisting lymph node (LN) metastasis is less than the mortality rate from esophagectomy. This study examines endoscopic and surgical outcomes, histological assessment of submucosal (sm) disease, factors influencing LN metastasis, and the safety of treating pT1b disease endoscopically. Histopathological reexamination recorded thickness, width and depth of sm invasion, grade, presence of lymphovascular invasion (LVI), resection margin status and tumor stage. Multivariate analysis was employed to evaluate the factors influencing survival and LN metastasis. Rate of LN metastasis for pT1 low-risk (LR: sm invasion < 500 μm, G1–2, no LVI) or high-risk (HR: sm invasion >500 μm, G3–4 or LVI) disease were analyzed. Ninety three patients underwent ER and 96 underwent esophagectomy. We demonstrate conflicting histological methods of sm disease reporting, which may explain the difference in LN metastasis rate between reported surgical & endoscopic series. Multivariate analysis confirmed age, T stage, and presence of LN metastases were the independent factors predicting poor prognosis. Tumor thickness as well as grade, T stage, LVI were predictors of LN metastasis. Rates of LN metastasis are <2% in LR sm1 disease, and >15% in HR sm1 disease. Pathological reporting of sm invasion should be updated for uniform analysis of endoscopic and surgical specimens. Following rigorous histopathological examination and within a close endoscopic follow-up regimen, pT1a and pT1b LRsm1 disease may be treated with curative intent endoscopically, whereas pT1b HRsm1-sm3 disease should be offered surgery.